2010
DOI: 10.1007/s10751-010-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment effects on spinel phase of Zn x Ni1 − x Fe2O4 and MnFe2O4 nanoferrites

Abstract: We report the effects of heat treatment on Zn x Ni 1−x Fe 2 O 4 (x = 0, 0.5 and 1.0) and MnFe 2 O 4 ferrite nanoparticles. The as-prepared compounds were sintered from 400 • C to 1100 • C. Pure ZnFe 2 O 4 (x = 1.0) and MnFe 2 O 4 could be obtained under low reaction temperature of 200 • C. NiFe 2 O 4 (x = 0) and Zn 0.5 Ni 0.5 Fe 2 O 4 (x = 0.5) nanoferrites crystallized with single phase cubic spinel structure after annealing at 600 • C. The single phase cubic spinel structure of these compounds was destroyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…ABO 3 ) on the materials. 16,17 Most importantly, the secondary phase exists at concentration >0.4. Although the density of these grain boundaries is reduced upon treating the powders at high temperature, secondary phase are still present in the catalyst layer at high concentrations of cerium; which may hinder the mobility of charge carriers and increases the electrical resistivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABO 3 ) on the materials. 16,17 Most importantly, the secondary phase exists at concentration >0.4. Although the density of these grain boundaries is reduced upon treating the powders at high temperature, secondary phase are still present in the catalyst layer at high concentrations of cerium; which may hinder the mobility of charge carriers and increases the electrical resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the bimetallic nature of spinels, the conductivity of ferrites can be tuned by substituting with a foreign metal, using different preparation conditions or using heat treatment. [16][17][18] Previous studies of MnFe 2 O 4 employed several synthesis methods, mostly to examine structural, electrical conductivity, magnetization and OER properties. 19,20 Recently, Shouheng Sun and his co-works found that similar ferrite system exhibits the ORR activity in alkaline solution, comparable to that of Pt.…”
Section: Introductionmentioning
confidence: 99%
“…For 57 Fe Mo¨ssbauer spectrometry, the τ m value is in order of 10 −8 s. It is also worth mentioning that, as previously reported for spinel nanoferrites, the Mo¨ssbauer spectra strictly depend on the chosen synthesis type and further sample processing. [5,16,17,22,24,25,34,35] In the paper of Hoque et al, [16] the influence of annealing on various physical properties, including the crystallites size of NiFe 2 O 4, is reported. Thus, the approach used by the authors reveals the emergence of a doublet line related to the processing of samples from its as-dried form to annealed up to 400 °C corresponding to the crystallites size from 2 to 4 nm.…”
Section: Hysteresis Loopsmentioning
confidence: 99%
“…Due to the fact that in this system the equal atomic percentages only refer to the used divalent metals, evidences of entropy stabilization are provided in the present work. Since it is known that manganese‐containing ferrites decompose at certain temperatures, this is a useful property to demonstrate whether an entropy stabilized spinel was obtained, since a multiphase state can be obtained that can be used to verify the first two requirements (see below) [29–31] . To gain a deeper insight and understanding of the compounds, we investigated the homogeneity at the nanoscale by TEM and determined the oxidation states and the distribution of cations on the octahedral and tetrahedral sites using X‐Ray Absorption Spectroscopy (XAS) and Mössbauer spectroscopy.…”
Section: Introductionmentioning
confidence: 99%